Stable Anilinyl Radicals Coordinated to Nickel: X‐ray Crystal Structure and Characterization. Issue 49 (4th November 2013) - Kochem, Amélie; Gellon, Gisèle; Leconte, Nicolas; Baptiste, Benoit; Philouze, Christian; Jarjayes, Olivier; Orio, Maylis; Thomas, Fabrice
Abstract Two anilinosalen and a mixed phenol‐anilinosalen ligands involving sterically hindered anilines moieties were synthesized. Their nickel(II) complexes 1, 2, and 3 were prepared and characterized. They could be readily one‐electron oxidized (E1/2=−0.30, −0.26 and 0.10 V vs. Fc+/Fc, respectively) into anilinyl radicals species [1]+, [2]+, and [3]+, respectively. The radical complexes are extremely stable and were isolated as single crystals. X‐ray crystallographic structures reveal that the changes in bond length resulting from oxidation do not exceed 0.02 Å within the ligand framework in the symmetrical [1]+ and [2]+. No quinoid bond pattern was present. In contrast, larger structural rearrangements were evidenced for the unsymmetrical [3]+, with shortening of one CorthoCmeta bond. Radical species [1]+ and [2]+ exhibit a strong absorption band at around 6000 cm−1 (class III mixed valence compounds). This band is significantly less intense than [3]+, consistent with a rather localized anilinyl radical character, and thus a classification of this species as class II mixed‐valence compound. Magnetic and electronic properties, as well as structural parameters, have been computed by DFT methods.